Hepatic mitochondrial and peroxisomal alterations in acutely ill malnourished Malawian children: A postmortem cohort study - Catriona M Ling; Tewabu F Sheferaw; Donna M Denno; Dennis Chasweka; Steve B Kamiza; Jaume Ordi; Christopher A Moxon; Kim Kats; Stanley Khoswe; Emmie Mbale; Frank Ziwoya; Abel Tembo; et al. (Elsevier, 2024)
Objectives: To describe and compare liver mitochondrial and peroxisomal histopathology by nutritional status in children who died following hospitalization for acute illness in Malawi. Methods: Liver tissue was collected using Minimally Invasive Tissue Sampling from eleven children under-five years old who died during hospitalization and were either non-wasted (n = 4), severely wasted (n = 4) or had edematous malnutrition (n = 3). Histology was assessed on hematoxylin and eosin stained slides. Mitochondrial and peroxisomal ultrastructural features were characterized using electron microscopy (EM) and immunofluorescence (IF). Results: Hepatic steatosis was present in 50 % of non-wasted and severely wasted children and all children with edematous malnutrition. Edematous malnutrition was associated with 56 % and 45 % fewer mitochondria than severe wasting (p < 0.001) and no wasting (p = 0.006), respectively, and abnormal mitochondrial morphology compared to severe wasting (p = 0.002) and no wasting (p = 0.035). Peroxisomal abundance was reduced in edematous malnutrition compared to severe wasting (p = 0.005), but did not differ from no-wasting. Conclusion: Edematous malnutrition is associated with reduced abundance and altered morphology of hepatic mitochondria and peroxisomes. Interventions targeting improvements in hepatic metabolic function may be beneficial in improving metabolism and reducing mortality in children with severe malnutrition, particularly in those with nutritional edema.